Womens Economic Empowerment through Micro-credit program: A Case of Thengamara Mohila Sabuj Sangha (TMSS) in Rural Bangladesh (Journal of Business and Technology (Dhaka), 2014)
The paper is an endeavor to assess womens economic empowerment through micro-credit program by evaluating different activities in various economic spheres in the rural area of Bangladesh. The study has been done utilizing both quantitative and qualitative methods. Using role of women in different economic spheres like household level, community level and broader arenas, a survey questionnaire was designed to collect data from 152 women following snow-ball sampling procedure and different statistical methods were applied to analyze the collected data. In addition, qualitative techniques like FGD and case study were used to validate the analyzed data. Finally, applying multiple regression method, the study revealed that different factors of household and community level e.g. ability of establishing rural cooperative banks, control of own poultry farm and its utilization, control of own jewelry and enjoyment, decision-making in land or equipment selling in an emergency and independent savings have been found significantly associated with the womens economic empowerment in the studied area. DOI: http://dx.doi.org/10.3329/jbt.v8i1-2.18285 Journal of Business and Technology (Dhaka) Vol.8(1-2) 2013; 41-62